Modelling of Fractionated Condensation for Off-Flavours Reduction from Red Wine Fermentation Headspace - Pereira, Maria João (2022)
Funding Information: Maria João Pereira acknowledges Fundação para a Ciência e Tecnologia for PhD fellowship SFRH/BD/119018/2016. This work was supported by the Associate Laboratory for Green Chemistry—LAQV, which is financed by national funds from FCT/MCTES (UIDB/50006/2020). Publisher Copyright: © 2022 by the authors.